HYBRID MODEL TO DESIGN AN AGRO-FOOD DISTRIBUTION NETWORK CONSIDERING THE QUALITY OF THE FOOD - González-Hernández, Isidro Jesús; Granillo-Macías, Rafael; Martínez-Flores, José Luis; Sánchez-Partida, Diana; Gibaja-Romero, Damián Emilio (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
In the agro-food supply chain, client’s satisfaction is mainly reflected in food freshness in such a way that quality has a direct relation with the selling price. This research work suggests a hybrid model for the design of a food distribution network that maximizes the farmers’ profits depending on the delivered quality by using a mixed integer linear programming model (MILP) and a discrete-event simulation model under certain stochastic parameters. The problem involves only one product (prickly pear), 93 farmers, 53 distribution centers and 27 markets. The results determined that the available offer (amount) of prickly pear of the 93 farmers must be sent to 29 distribution centers to satisfy the demand of the market, the delivered quality of the fruit at the market is in an interval from 84% and 94%.